2017
DOI: 10.1002/arch.21441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functions of the signal peptidase complex in the midgut of Tribolium castaneum

Abstract: Signal peptidase complexes (SPCs) are conserved from bacteria to human beings, and are typically composed of four to five subunits. There are four genes encoding SPC proteins in the red flour beetle, Tribolium castaneum. To understand their importance to insect development, double-stranded RNA for each SPC gene was injected into red flour beetles at the early larval and adult stages. Knockdown of all four signal peptidase genes was lethal to larvae. Moreover, larvae had difficulty with old cuticle ecdysis. Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Of these 3 families, PCs, which are related to the bacterial ‘subtilisin’ [10] have shown the greatest diversification through the evolution of multicellularity. While 4 to 5 SPs, and 1 to 2 CPs are typically been found in a range of both unicellular and multicellular organisms [1113], PCs show varied distribution across the tree of life, with yeast Saccharomyces cerevisiae species possessing 1 (Kexin) [4], D . melanogaster having 3 PCs, 2 of which being distinct variants of the same convertase ‘Furin’ [14], while Caenorhabditis elegans possesses 5, 2 of which (blisterase and aex-5) are nematode specific, with blisterase generating 9 isoforms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of these 3 families, PCs, which are related to the bacterial ‘subtilisin’ [10] have shown the greatest diversification through the evolution of multicellularity. While 4 to 5 SPs, and 1 to 2 CPs are typically been found in a range of both unicellular and multicellular organisms [1113], PCs show varied distribution across the tree of life, with yeast Saccharomyces cerevisiae species possessing 1 (Kexin) [4], D . melanogaster having 3 PCs, 2 of which being distinct variants of the same convertase ‘Furin’ [14], while Caenorhabditis elegans possesses 5, 2 of which (blisterase and aex-5) are nematode specific, with blisterase generating 9 isoforms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the GO terms that were highly represented at all three temperatures were biological processes pertaining to ‘signal peptide processing’ and ‘protein ufmylation’, localized to the ‘signal peptidase complex’ and with ‘protein disulfide isomerase activity’ (and the related GO term of ‘intramolecular oxidoreductase activity transposing S-S bonds’) (Supplementary figure 2A, 2B, 2D and Supplementary table 1). Most of the gene products associated with these terms are conserved across phyla and involved in protein folding, degradation, and trafficking to and from the endoplasmic reticulum (Gerakis, Quintero, Li, & Hetz, 2019; Guan et al, 2018). One exception to this is protein disulfide isomerase (Supplementary table 2), which expresses dual oxidoreductase-isomerase functions and serves as an antioxidant in an Aedes albopictus cell line infected with DENV (T.-H. Chen et al, 2011), but has also been shown to be essential for blood feeding, survival, and oogenesis in ticks (M. Liao et al, 2008).…”
Section: Resultsmentioning
confidence: 99%